2016
DOI: 10.1038/srep38819
|View full text |Cite
|
Sign up to set email alerts
|

A dissociation between consolidated perceptual learning and sensory adaptation in vision

Abstract: Perceptual learning refers to improvement in perception thresholds with practice, however, extended training sessions show reduced performance during training, interfering with learning. These effects were taken to indicate a tight link between sensory adaptation and learning. Here we show a dissociation between adaptation and consolidated learning. Participants trained with a texture discrimination task, in which visual processing time is limited by a temporal target-to-mask window defined as the Stimulus-Ons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Third, our findings support the idea that learning is facilitated when the cortical processes underlying the task are stimulated while in an aroused state derived by task performance (Wright et al, 2010), and indicate the possibility to use tRNS to rapidly reach this optimal state. Importantly, our study further indicates the benefits of short but effective training sessions, an ideal condition to promote learning (Censor and Sagi, 2008;Censor et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Third, our findings support the idea that learning is facilitated when the cortical processes underlying the task are stimulated while in an aroused state derived by task performance (Wright et al, 2010), and indicate the possibility to use tRNS to rapidly reach this optimal state. Importantly, our study further indicates the benefits of short but effective training sessions, an ideal condition to promote learning (Censor and Sagi, 2008;Censor et al, 2016).…”
Section: Discussionsupporting
confidence: 55%
“…Performance then tapered off. Performance deterioration within a single testing session is not uncommon 7 , which can be attributed to sensory adaptation or fatigue. Because sensory adaptation depends on the number of trials and the number of trials was the same for the two non-rating groups and for the two rating groups, their differences were likely due to a difference in the fatigue effect.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, our TDT task implemented variable ISIs within each session through the method of descending limits, whereas texture discrimination training in Beer et al (2013) employed a fixed ISI. Previous work investigating the dynamics of consolidation of PL has shown that the latter training method induces less sensory adaptation and enhances texture discrimination learning, compared with the former (Harris & Sagi, 2015;Censor, Harris, & Sagi, 2016).…”
Section: Potential Mechanisms Underlying Cholinergic Facilitation Of mentioning
confidence: 94%